Total Quality Management (TQM) : a Model for the Sustainability of Projects and Programs in Africa. - Morfaw, John N. (Rowman & Littlefield Pub. Group, 2009)
Total Quality Management and Project Management have a symbiotic relationship in their planning, design, analysis, implementation, monitoring, and evaluation, as well as other related processes. This book accentuates the relationship between Total Quality Management and Project Management and other contemporary management concepts. These contemporary concepts include Six Sigma Methodology, International Organization for Standardization (ISO), Capacity Building, Business Re-engineering, Knowledge Management, Configuration Management, SWOT Analysis, and Total Quality Leadership, as well as fundamental business management concepts such as leadership dynamics, quality assurance, quality control, and continuous quality improvement. The book evaluates and analyzes the relationship between Total Quality Management and Human Resource Management, Public Relations Management, Marketing Management, Risk Management, Project Proposal Writing, and Resource Coordination and Management. Total Quality Management gives an exploratory overview of the contributions of certain national and international organizations that operate in Africa towards an effective and efficient delivery of products and services, especially on the implementation of capacity building programs in Africa, such as The World Bank, AfDB, CDC, PAID, ACBF, UNDP, AAPAM, CAFRAD, NEPAD, and others.